Influence of piston and magnetic coils on the field-dependent damping performance of a mixed-mode magnetorheological damper. (30th March 2016) - Zeinali, Mohammadjavad; Mazlan, Saiful Amri; Choi, Seung-Bok; Imaduddin, Fitrian; Hamdan, Lailatul Hamidah
Abstract: This work presents a 2D simulation study of a mixed-mode magnetorheological (MR) damper in which the influence of the geometric elements of the piston and magnetic coil on the MR damper's performance is investigated by using the Ansoft Maxwell software tool. Four results of the simulation, which are magnetic flux density ( B ), MR fluid yield stress ( τ 0 ), and are used to compare the performance of the MR damper. Multiplication of the yield stress by the active operating mode length represents the variable portion of the active (on-state) damping force of the flow mode motion, while the value of represents the active damping force of the shear mode motion. The contribution of each operating mode (shear and flow) is related to the mixed-mode geometry and piston velocity. Therefore, each operating mode is evaluated separately. In this work, a total of 154 simulations are done in which 74, 20 and 60 simulations are conducted to analyse the effect of the piston radius, coil dimensions (width and length) and coil boundary lengths, respectively, on the performance of the MR damper. The simulation results show that increasing the piston radius can increase the value and reduce the value. For a given area of magnetic coil housing, a greater housing length in the axial direction of the piston can increase the achieved yield stress of the MR fluid and hence consequently the performance of the MR damper. A minimum boundary length is needed around the magnetic coil in order to attain a supreme magnetic field distribution. However, there is an optimised value for axial coil boundary lengths, which are the lengths of the upper and lower mixed-mode areas.